Constructing fluorinated transport pathways in polyesteramide membranes for efficient desalination - Chenchen Zhang; Yi Zhao; Huanping Wu; Kexin Lin; Qi Huang; Wenxiong Shi; Jianqiang Meng (Desalination, 2026)

Flash Joule heating enables defect and nitrogen configuration engineering in lignin-derived carbon for broadband electromagnetic wave absorption - Chenchen Wang; Jiayi Zhong; Chuanshuang Hu; Junda Yang; Yonghui Zhou; Weiwei Zhang; Jiangtao Xu; Xiuyi Lin (Chemical Engineering Journal, 2026)

Sustainable mechanochromism and photochromism achieved by incorporating rhodamine into dialdehyde bacterial cellulose - Zheyu Shen; Qiuhao Yi; Bianjing Sun; Yalei Qiao; Xinyu Chen; Chenchen Qin; Lin Shi; Hongxia Qu; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

NCSSD-YOLO: a non-causal state space duality-based instance segmentation model for pacific white shrimp - Weiqiang Ni; Chenqing Zhang; Yiqing Zhang; Siyi Li; Haitao Wang; Chenchen Wu; Lin Luo; Qinglang Liang; Zequn Peng; Shenghua Li; Yanqing Chen; Shiyin Chen; et al. (Aquaculture International, 2026)

Efficient photocatalytic degradation of acetamiprid via Fe2O3/Fe-TCBPE activating peroxymonosulfate - Chenchen Li; Zhourui Wu; Rui Xu; Tai Xiang; Lin Tian; Yong Zhang (Journal of Environmental Sciences, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Hierarchically porous UiO-66-(OH)2@COF-OMe composites with multiple binding sites for synergistic extraction of polybrominated diphenyl ethers from surface waters - Jingpu Tang; Wentao Lan; Hongyan Zeng; Chenchen Lin; Xiaoping Wu (Journal of Hazardous Materials, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

In situ-based spectral characteristics of first-year landfast ice in eastern Liaodong Bay, Bohai sea - Qingkang Hou; Yu Yan; Zhikun Lin; Chenchen Yao; Jiayu Ding; Jinghan Xu; Chenyu Shu; Lei Ren; Yingjun Xu (International Journal of Remote Sensing, 2026)

In situ spectral analysis of sea ice contaminated with multiple substances in Liaodong Bay, Bohai Sea - Jinghan Xu; Yu Yan; Zhikun Lin; Qingkang Hou; Jiayu Ding; Chenchen Yao; Lei Ren; Chenyu Shu; Yingjun Xu (Marine Pollution Bulletin, 2026)

Construction of SnO2/Bi2O2CO3 Z-type heterojunction for photocatalytic degradation of humic acid under sunlight - Muxi Zhang; Chenchen Liao; Bin Dong; Wenjie Lin; Yu Chen; Penghui Yao; Xiaojie Sun; Hongxia Zhang (Environmental Research, 2026)

Vernalization-responsive intronless genes in faba bean and the development of KASP markers - Xiaocen Liu; Jinyang Liu; Jiali Huang; Shuoqian Zhao; Shengqi Chen; Yun Lin; Qiang Yan; Jingbin Chen; Chenchen Xue; Ranran Wu; Yonghai Sun; Yuhua He; et al. (Plant Cell Reports, 2026)

Magnetic aptasensor with UiO-MOFs-mediated orientation-ordered aptamers for sensitive portable test of okadaic acid toxin - Qing'ai Chen; Yuwei Zhou; Guobin Huang; Chenchen Lin; Xucong Lin (Analytica Chimica Acta, 2026)

DDX21 nuclear-cytoplasmic shuttling recruits RPS18 to viral dsRNA to promote CSFV replication - Bingke Li; Bolun Zhou; Chenchen Sun; Shurou Li; Ye Bai; Ruibo Zhao; Yiwan Song; Yintao He; Lin Yi; Hongxing Ding; Shuangqi Fan; Jinding Chen; et al. (Veterinary Microbiology, 2026)

Potential disease-related risk of saccharin in ovarian cancer: An integrative multi-evidence analysis - Yang Song; Hao Yang; Yanchun Wang; Chenchen Lin; Xuemei Wang (Reproductive Toxicology, 2025)

Schiff base-grafted bacterial cellulose-PCL composites: Humidity/temperature-driven hydrogen bond reconfiguration for mechanically adaptive nanofiber - Chenchen Qin; Bianjing Sun; Xinyu Chen; Du Ping; Wuxin Bai; Lin Shi; Ahsan Nazir; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2025)

Integrated, self-powered humidity/iontronic pressure sensors for complex respiratory pattern recognition - Senrong Ye; Junxian Li; Haowei Kong; Zijun Pan; Haohan Wu; Zhanghao Lin; Chenchen Bian; Gengzhe Shen; Chi Zhang; Weidong Song; Zheng Liu; Xin He (Chemical Engineering Journal, 2025)

Two new alkaloids identified from herb Delphinium trichophorum French, a famous Tibetan drug “Gebu Dilu” - Siyuan Liu; Yuansheng Zou; Zeren Dawa; Fangle Liu; Meiqi Wang; Chenchen Zhu; Chaozhan Lin (Natural Product Research, 2025)

Gas content and fracability in deep marine shales: Insights from laminar heterogeneity and reservoir characteristics - Xiao Xiao; Jizhen Zhang; Jianguo Wang; Wei Guo; Wei Lin; Denglin Han; Chenchen Wang (Journal of Environmental Chemical Engineering, 2025)

Synergistic HRP/Biotin encapsulation in DNA nanoflowers via RCA: A path to stabilized, streamlined ELISA platform - Xinglin Wu; Chengqun Chen; Chenchen Lin; Jiabin Wang; Qibiao Weng; Xucong Lin (Analytica Chimica Acta, 2025)

Asymmetric gradient-structured PPy@bacterial nanocellulose aerogels enable broadband microwave absorption via synergistic polarization-conduction loss - Xi Lin; Chenchen Wang; Chaoqun Zhang; Qi Guo; Chuanshuang Hu; Yi Yang; Yonghui Zhou; Xiuyi Lin; Weiwei Zhang; Jiangtao Xu (Chemical Engineering Journal, 2025)

Negative regulation of hippo-mediated antiviral response targeted WSSV in Penaeus vannamei - Hong Shi; Wenyang Lin; Yibin He; Jie Ren; Yiwen Jian; Zhihao Huang; Caozhi Huang; Chenchen Zou; Lingwei Ruan (Aquaculture, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Machine learning-assisted SERS sensor for fast and ultrasensitive analysis of multiplex hazardous dyes in natural products - Chengqi Lin; Cheng Zheng; Bo Fan; Chenchen Wang; Xiaoping Zhao; Yi Wang (Journal of Hazardous Materials, 2025)

The impact of digital economy on energy rebound effect in China: A stochastic energy demand frontier approach - Chenchen Huang; Boqiang Lin (Energy Policy, 2025)

The role of pattern recognition receptors in the innate immune system of Chinese mitten crab (Eriocheir sinensis) - Chenchen Shi; Ta-Hui Lin; Chen Qu (Fish & Shellfish Immunology, 2024)

Heteronuclear FeN3-CuN3 atom pairs coordination engineering of single-atom catalysts for water splitting and Zn-Air batteries - Yinglin Zhang; Bo Yan; Chenchen Ji; Tingting Wei; Wenbin Niu; He Lin; Yulin Shi (Chemical Engineering Journal, 2024)

A novel nitric oxide-driven nanomotor for synergistic treatment of ischaemic stroke: Enhanced deep brain penetration and therapeutic efficacy - Zhicheng Xiao; Yi Li; Ting Chen; Chenchen Xie; Jun Liao; Pu Lin; Zhe-Sheng Chen; Yan Qiu; Jian Cai; Chuan Zhang; Tingfang Wang (Chemical Engineering Journal, 2024)

A novel subsurface adjustable dam for preventing active seawater intrusion in coastal aquifers - Qinpeng Chang; Chenchen Gao; Xilai Zheng; Yucheng Lin; Xiaoran Song (Frontiers in Marine Science, 2024)
Subsurface physical barriers are widely used to prevent seawater intrusion in the world. After the construction of physical barriers, the residual saltwater is trapped upstream the barriers. Traditional physical barriers, including cutoff walls and subsurface dams, are fixed in structure and fail in prohibiting active seawater intrusion. In this work, a novel subsurface adjustable dam, composed of dam bodies and sluice gates, was designed to prevent active seawater intrusion and store groundwater flexibly according to seasonal variations in precipitation. We set three-dimensional field-scale numerical simulations to compare the control effects of adjustable dams, cutoff walls, and subsurface dams. The results revealed that the traditional subsurface physical barriers could mitigate the velocity of active seawater intrusion but were inadequate in completely preventing the intrusion process. Furthermore, although the traditional physical barriers temporarily alleviate the residual saltwater during the wet periods, the saltwater wedge would subsequently invade during next dry periods. Thus, the salt mass in the aquifer of traditional physical barriers scenarios exhibited a gradual annual increase. In contrast, the novel subsurface adjustable dam demonstrated the ability to prevent active seawater intrusion and remove the residual saltwater. During the dry periods, characterized by low precipitation recharge, the sluice gates were closed to obstruct the path of active seawater intrusion. Conversely, during the wet periods with abundant precipitation, the sluice gates were opened, facilitating the gradual removal of the residual saltwater. The flexible adjustment mechanism of subsurface adjustable dams resulted in a annual decrease in both the seawater intrusion length and the salt mass in the entire aquifer. These findings underscore the efficacy of the subsurface adjustable dam as a measure for preventing active seawater intrusion and simultaneously eliminating the residual saltwater.

Recycling of expired cow milk for constructing multifunctional biomass nonfluorinated chromatic paint with superhydrophobicity - Cheng Chen; Chenchen Gao; Kaige Lin; Jing Zhang; Zhiwei Zhang; Yifan Jing; Yuanshu Xiao; Guohua Shan; Cheng Xie (Chemical Engineering Journal, 2024)

Parental material and climate jointly determine the biomass and diversity of soil microbial communities along an elevational gradient on a subtropical karst mountain - Xianjin He; Lian Zeng; Guangyu Zhu; M. D. Farnon Ellwood; Lihua Zhou; Junlong Huang; Chenchen Wang; Wei Li; Dunmei Lin; Pei Wei; Shijun Liu; Min Luo; et al. (Journal of Biogeography, 2024)
Aim Climate is widely understood to determine elevational patterns of soil microbial communities, whereas the effects of parental material are uncertain. Changes in the composition of parental materials along elevational transects could also affect soil microbial communities by influencing soil pH and nutrient availability. Here, we aim to illustrate the combined effects of climate and parental material on the biomass and composition of soil microbial communities along an elevational transect. Location A subtropical forest on a karst mountain (Mt. Jinfo), China. Taxon Bacteria and Fungi. Methods We use phospholipid fatty acid analysis (PLFA) and DNA amplicon high‐throughput sequencing to determine biomass and diversity patterns of soil microbial communities along a subtropical elevational gradient with contrasting parental materials (limestone and clasolite). Results We observed that the microbial communities were more diverse (α‐diversity) and productive (biomass) on limestone than on clasolite. Additionally, we found that parental material played a role in shaping the composition (β‐diversity) of soil microbial communities along the elevational gradient. The impact of climate on soil microbial communities was found to be significant, albeit relatively weak. Structural equation models provided evidence for both direct and indirect effects of climate and parental material on microbial biomass and α‐diversity along the elevational gradient. Notably, the changes in soil pH, influenced by both parental material and climate, were identified as a key factor driving these effects. Main Conclusions Our results underline the importance of both climate and parental material variations in space‐for‐time studies investigating soil microbial communities along elevational gradients.

Betulinic acid induces apoptosis of HeLa cells via ROS-dependent ER stress and autophagy in vitro and in vivo - Ping Chen; Xueer Zhang; Qiaomiao Fang; Zhongxiang Zhao; Chaozhan Lin; Yuan Zhou; Fangle Liu; Chenchen Zhu; Aizhi Wu (Journal of Natural Medicines, 2024)

Digitalizing river aquatic ecosystems - Yaohui Bai; Hui Lin; Chenchen Wang; Qiaojuan Wang; Jiuhui Qu (Journal of Environmental Sciences, 2024)

Fluorescence detecting glycopeptide antibiotics via a dynamic molecular switch - Xiaomei Zou; Yanting Lin; Shihui Zhang; Tao Deng; Ximing Xu; Yingchun Zhou; Zhihui Liu; Weiguo Lu; Qingzhong Hu; Chaozhan Lin; Chenchen Zhu; Fang Liu (Analytica Chimica Acta, 2024)

Hydrodynamic behavior of freshwater-saltwater mixing zone in the context of subsurface physical barriers - Qinpeng Chang; Tianyuan Zheng; Chenchen Gao; Xilai Zheng; Yucheng Lin; Xiaoran Song; Marc Walther (Journal of Environmental Management, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Phosphorylation regulation of Lv-β-catenin of Litopenaeus vannamei by an immediate early protein WSV083 to reduce cell adhesion - Wenhao Wu; Chenchen Zou; Hong Shi; Chuanqi Wang; Wenyang Lin; Yueling Zhang; Yibin He; Lingwei Ruan (Aquaculture, 2024)

Identifying ARG-carrying bacteriophages in a lake replenished by reclaimed water using deep learning techniques - Donglin Wang; Jiayu Shang; Hui Lin; Jinsong Liang; Chenchen Wang; Yanni Sun; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Promoting decarbonization in the power sector: How important is digital transformation? - Chenchen Huang; Boqiang Lin (Energy Policy, 2023)

ATP-responsive and functionalized framework nucleic acid for synergistic radio-immunotherapy - Yuxin Zhang; Yuxi Zhan; Chenchen Mao; Guo Li; Yuxuan Zhao; Ye Chen; Yunfeng Lin (Chemical Engineering Journal, 2023)

Preparation, characterization, and evaluation of the antitumor effect of kaempferol nanosuspensions - Wen He; Junfeng Zhang; Jiale Ju; Yinghua Wu; Yuxi Zhang; Lin Zhan; Chenchen Li; Yanli Wang (Drug Delivery and Translational Research, 2023)

Localized host-rock porosity near sealed fractures at 7 km depth: Geochemical evidence of deep-seated porosity controls - Denglin Han; Jizhen Zhang; Chenchen Wang; Wei Lin; Rui Yuan; Xin Nie; Juan Zhang (Journal of Structural Geology, 2023)

Effect of five polyphenols on the stability of purple cabbage anthocyanins in simulated beverage systems containing L-ascorbic acid - Menghua Lin; Chenchen Sun; Qingchao Gao; Zhiyong Zhang; Ying Liang; Shulin Wang (Food Packaging and Shelf Life, 2023)

Paternal genetic intergenerational and transgenerational effects of cadmium exposure on hormone synthesis disorders in progeny ovarian granulosa cells - Yi Sun; Chenyun Zhang; Lingfeng Luo; Hao Lin; Chenchen Liu; Wenchang Zhang (Environmental Pollution, 2023)

How will promoting the digital economy affect electricity intensity? - Boqiang Lin; Chenchen Huang (Energy Policy, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Geological and climatic histories likely shaped the origins of terrestrial vertebrates endemic to the Tibetan Plateau - Jiekun He; Siliang Lin; Chenchen Ding; Jiehua Yu; Haisheng Jiang (Global Ecology and Biogeography, 2021)
Aim The Tibetan Plateau (TP) hosts many endemic species, but questions regarding when and from where these species originated have not been comprehensively answered. Here, we provide a synthesis of the biogeographical history of terrestrial vertebrates endemic to the TP and investigate the potential drivers of their spatio‐temporal origins. Location Tibetan Plateau and its surrounding regions. Time period Cenozoic. Major taxa studied Terrestrial vertebrates. Methods We used dispersal–extinction–cladogenesis models based on time‐calibrated phylogenies to reconstruct the ancestral ranges of 174 endemic TP species and compiled the ancestral ranges and age estimates of their dispersal events. We generated a possibility map of source areas for endemic TP species by counting the incidence of non‐TP sister clades in 110 km × 110 km grid cells. We used generalized linear mixed models to assess the relative importance of historical processes and environmental factors in explaining the geographical variations in the source areas. We created subsets based on four vertebrate classes to test whether the dispersal events varied spatially and temporally among taxonomic groups. Results We found that the endemic species colonized the TP as early as 55 Ma, and that the main colonization phase started to increase around 15 Ma and peaked after 6 Ma. The major source areas of endemic TP species include the Hengduan Mountains, the Himalayas, and Central Asia. Elevation difference had the strongest effect on the source areas, followed by geographical distance. The spatio‐temporal origins of species endemic to the TP and the potential drivers showed significant differences among vertebrate classes. Main conclusions Our study supports the hypothesis that endemic TP species originated from various zoogeographical regions at different times and highlights the important roles of the TP uplift and past climatic changes for determining the spatio‐temporal origins of endemic TP species.

Effects of Single-Dose and Long-Term Ketamine Administration on Tau Phosphorylation–Related Enzymes GSK-3β, CDK5, PP2A, and PP2B in the Mouse Hippocampus - Yanning Li; Gehua Wen; Runtao Ding; Xinghua Ren; Chenchen Jing; Lin Liu; Jun Yao; Guohua Zhang; Yan Lu; Baoman Li; Xu Wu (Journal of Molecular Neuroscience, 2020)